Mould Filling In Electronic Packaging - Heng, Chai Wei (Universiti Sains Malaysia, 2005)
This final year project focuses on the study of flow in encapsulation processes of electronic packaging in an industry. The present study is using a program, which is written in Matlab language. Characteristic Based Split (CBS) method is utilized in this program to analyze and model the fluid flow in a single cavity mold of the encapsulation process. The velocity field obtained from CBS method is thus used in pseudo-concentration algorithm, which uses the VOF technique to track the fluid front for each time step. Finite element method (FEM) is employed in all the analyses to reduce the governing partial differential equations to algebraic equations. Parametric studies have been carried out to study how the dimensions and parameters of the gate and die/chip affect the flow filling’s behavior. Parametric studies showed by altering the dimensions of the mold tools, the filling time for certain cases would be different due to different hydraulic resistances and pressure at the entrance of the mold cavity. These parametric studies conducted for the purpose to achieve balanced mold filling in the encapsulation process.